Divide and Rule: Israel's Tactics Regarding the Jerusalem Question and America's Response, 1949–1950. Issue 1 (2nd January 2017) - Heimann, Gadi
Abstract: In 1949–1950, an interesting diplomatic affair took place for which details have not yet being disclosed. The Israelis who were unable to reach an agreement with the Jordanians over Jerusalem, advanced solutions in which the latter will pay the major price. However, the US was not interested in forcing a solution on the Jordanians nor to see them internationally isolated. Preventing such a development was far more important for them than promoting the internationalization plan. Thus US acted to sabotage Israelis maneuvers believing that putting the blame of failure on both sides suit best their interests. Therefore, the belief that the Americans took a passive and neutral stand over the Jerusalem question does not conform to reality. Instead, they were engaged vigorously, although mostly behind the scene, undermining the 1949 resolution.